Critical infrastructures: threats, vulnerabilities and protection - Protić, Danijela D. (Vojnotehnički glasnik / Military Technical Courier, 2016)
This paper presents six critical infrastructure sectors: electric power systems, energy sources and supply, manufacturing, transport and storage of hazardous substances, traffic and transportation, information-telecommunication infrastructure, and supply with basic viands. The sources of adverse unwanted events due to accidents, technical faults, natural disasters, and human error are presented. Prediction and prevention of these events are explained in details.
Keywords: Transportation; protection; vulnerabilities; threat; critical infrastructure; hazards